Are study populations in trials of antidepressants and psychotherapy comparable? A retrospective case study of two parallel running trials for multi- organ functional somatic disorder. (May 2022) - Agger, Johanne Liv; Schröder, Andreas; Ørnbøl, Eva; Jensen, Jens Søndergaard; Pedersen, Heidi Frølund; Fink, Per; Gormsen, Lise Kirstine
Highlights: The eligibility criteria resulted in a less complex and less severely impaired study population for the pharmacological trial. The more complex and more severely ill patients were to a large extent eligible for the psychotherapy trial. This should be taken into account when designing trials of psychotherapy and pharmacotherapy and in the interpretation and implementation of trial results. Abstract: This study retrospectively compares two previous parallel running, randomized, controlled trials of pharmacotherapy (imipramine) and psychotherapy (acceptance and commitment therapy) for multi-organ functional somatic disorder (FSD). Differences in demographics, psychiatric comorbidity, illness severity, and illness duration associated with eligibility for the two trials and patients' willingness to participate are explored using linear or binary regression models. 418 patients with multi-organ FSD was included. We found that 377 (95%) were eligible for psychotherapy and 257 patients (61%) for pharmacotherapy. Patients eligible for pharmacotherapy were less severely impaired, less often received disability pension, reported shorter illness duration and experienced less psychological distress than patients eligible for psychotherapy. Whilst exclusion criteria for both trials differed markedly, it was not possible to clearly identify patient or illness characteristics associated with patients' willingness to participate. The study showed that trial-specific exclusion criteria led to the selection of less complex and less severely impaired patients in the pharmacological trial in this sample of multi-organ FSD. Our findings have important implications for the interpretation and comparability of RCT results of different treatments in multi-organ FSD and may point to some common flaws in study design and interpretation of pharmacological vs. psychotherapeutic intervention trials in psychiatry.